The Creative Process Of Musafir Isfanhari In The Creation Of A Musical Work "Keroncong Keluarga Berencana" (Jurnal Seni Musik, 2022)
Musafir Isfanhari is one of the senior music artists in East Java. The man known as the arranger and composer has created many works of music. One of Isfanhari's phenomenal musical works is the song Keroncong Keluarga Berencana . The purpose of this research is to examine the creative process of creating keroncong KB song works by Musafir Isfanhari. Research uses descriptive qualitative methods using phenomenological approaches. The data collection techniques in this study use interview, observation and documentation techniques. The results and highlights in this article outline Isfanhari's biography, the work and creative process of the creation of the song Keroncong Keluarga Berencana. Discussion of the creative process based on the John Livingston category among others; (1) the process of filling a well, or filling the mind with materials and experiences related to the phenomenon of promoting Keluarga Berencana programs. (2) Sudden vision through suggestion based on distraction or interference from the outside that affects the suggestions of Isfanhari's mind in making lyrics and melodies. (3) Completion of the work, which contains the process of meeting with O.K Getah Jaya, the training process to introduce the song Keroncong KB to the general public. The conclusion in this study is that the process of creating art, apart from containing elements of art or musicals, can also be associated with several other elements such as psychological theory and the concept of creativity.